Effect of increased uncertainty on financial asset holding - Frimpong, Albert (International Journal of Accounting and Economics Studies, 2014)
Much is known from theoretical and empirical literature about the relationship between firms’ investment decisions and increased uncertainty; thus, firms have preference for liquid assets to capital formation under uncertainty because investment in capital formation is not easily reversible. So, whether uncertainty has effect on financial investment is a moot point to consider. This paper investigates the relationship between financial information and financial asset holding. A model is formulated and empirical evidence provided to throw more light on the relationship. The paper finds that financial information reduces uncertainty regarding investment in financial assets. The paper recommends to financial investors to gather information regarding the investment to minimise the risks associated with losing value for the money invested and also to avoid investment mistakes. Also, the paper finds that financial investors, adopt “wait and see” approach and delay investment with increased uncertainty. Stakeholders should put measures in place to prevent (negative) rumors regarding financial institutions because it cripples financial investment as prospective investors would decrease their investment and wait in order to increase their information about the true state of the market before they make investment. Also, policy makers should ensure macroeconomic stability and safe political environment for the operation of the financial market. Keywords: Financial Assets, Uncertainty, Financial Information, Investment, Interest Rate, Financial Investor.